Trauma and Daseinsanalysis: Ontological aspects of traumatic experiences beyond the neurotic structure (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
This study reflects on traumatic suffering and provides clinical guidelines within the framework of Daseinsanalysis. It explores how ontic and ontological dimensions of trauma interact, showing that even in violent experiences, the ontological foundation of human existence is crucial for understanding trauma.
Keywords: Trauma; PTSD; angst; Daseinsanalysis; Alice Holzhey-Kunz; Martin